Treasured exceptions: association of morphoanatomical leaf traits with cup quality of Coffea arabica L. cv. “Catuaí ” - Perez-Molina, Junior Pastor (2021)
The morphoanatomical characteristics of leaves were associated with altitude, hillside, and the cup quality of coffee produced in the Matas de Minas region. Although the small magnitude, there are correlations between cup quality with altitude and morpho-anatomical traits. Despite facing the differences of management inherent to 363 sampling sites, Northwestern hillside had significant lower cup quality, whereas only stomata density (SD) and thickness of the leaf epidermis in the adaxial face (AdET) showed significant differences between hillsides. Altitude, leaf mass per area (LMA) and SD, and to a lesser extent the thickness of the leaf epidermis in the abaxial face (AbET), were correlated (Spearman’s correlation) with cup quality. Interestingly, AbET correlations were negative. Mantel’s test significant correlations were found between coffee cup quality vs. altitude, LMA and petiole phloem area (PPhA). The spatial autocorrelation was significant only with LMA. Also, SD, to a lesser extent, was associated with cup quality. Despite the complexity of the association among the environment, plant growth and development, this is the first report to associate morpho-anatomical features of the leaf with the coffee cup traits. Even with the expectation of genotype/species vs environment interactions, and the influence of other parameters associated with post-harvest, roasting and brewing, the evaluation of LMA, SD, AdET, AbET and the thickness of the palisade parenchyma (PPT) allow a novel approach to access coffee cup quality.